Lodz – the centre of creative industries - Szyjkowska, Dominika (Creativity in Business Practice. Part 2, 2019)
The chapter describes various actions undertaken by the city of Lodz in order to create a center of creative industries and change the existing image of the city at the same time. The aim of the paper is to show a strategic action plan which contributes towards creating the center of creative industries in Lodz.